2021
DOI: 10.1007/s11356-021-13779-9
|View full text |Cite
|
Sign up to set email alerts
|

The preliminary evaluation of differential characteristics and factor evaluation of the microbial structure of rural household toilet excrement in China

Abstract: Recent studies on the microbial community composition of human excrement after rural household toilet treatment are unclear regarding the effects and risks of using recycled products as fertilizers in agriculture. In this study, we used Illumina high-throughput sequencing to investigate the microbial community structure of the excrement from 50 Chinese rural household toilets on a spatial scale, and we evaluated the impact of select geochemical factors on the bacterial and fungal communities in the human excre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…A large-scale survey revealed that the proportion of pathogenic bacteria in the effluent from septic tanks is very low [44], and ensured environmental health and agricultural application safety. While approximately 86% of the households stated that they would prefer their excreta to be used in agriculture as fertilizer [45], there is no instructional document to teach farmers how to use blackwater to fertilize, and the usual practice of farmers is to return all the collected blackwater to the field.…”
Section: Feasibility and Prospect Of Returning Blackwater To The Fieldmentioning
confidence: 99%
“…A large-scale survey revealed that the proportion of pathogenic bacteria in the effluent from septic tanks is very low [44], and ensured environmental health and agricultural application safety. While approximately 86% of the households stated that they would prefer their excreta to be used in agriculture as fertilizer [45], there is no instructional document to teach farmers how to use blackwater to fertilize, and the usual practice of farmers is to return all the collected blackwater to the field.…”
Section: Feasibility and Prospect Of Returning Blackwater To The Fieldmentioning
confidence: 99%
“…In the process of rapid economic development and the continuous advancement of rural urbanization, the huge population and remote geographical location of rural areas have meant that they have long-term disadvantages in terms of infrastructure, science and technology, and development awareness, especially with regard to rural toilets, which are considered to be the most difficult to manage, and there is a lack of rural infrastructure in developing countries Li et al, 2021). Non-hygienic toilets, such as open toilets, in which feces cannot be safely stored quickly enough, can cause intestinal infectious diseases such as dysentery and typhoid fever, thereby increasing the risk of death from infectious diseases Gao et al, 2021). Some studies have also indicated that the contributions of total nitrogen and total phosphorus from toilet sewage accounted for 84% of the total pollutant load of rural domestic sewage (Angelakis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%